Proteolytic activity characterization of bacteria isolated from Malaysian traditional fermented food [electronic resource] - Najihah Ismail, 1989- author; Haryati Jamaluddin, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2014)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2014